An Analysis of Repetition Used in Shawn Mendes' Selected Song Lyrics - Lestari, Della Amelya Indah; Arifin, M. Bahri; Rahayu, Famala Eka Sanhadi (Fakultas Ilmu Budaya Universitas Mulawarman, 2021)
The objective of this research was to describe the types of repetitions in Shawn Mendes’ selected song lyrics to find their functions in the selected song lyrics that the researcher chooses for this study. This study employed a qualitative design with a stylistic approach that aims to the types and functions of repetitions in Shawn Mendes’ song lyrics. The result of this study shows that all nine types of repetitions were found in this study. There are forty-six alliterations, twenty-six assonances, twenty-one consonances, five refrains, four feminine rhymes, five masculine rhymes, two internal rhymes, eighteen end rhymes, and five approximate rhymes. And besides that, it is possible to have more than one type of repetitions and functions in one data. The most dominant repetition in this study is alliteration. After categorizing and interpreting the data, the researcher found three out of four functions of repetition found such as; to reinforce meaning, to emphasize certain words, and to link up or contrast words. And also based on the result mention above, the researcher can conclude that Shawn Mendes has a narrative style of writing because of the way he wrote his lyrics that has the repetition of persuasive lines that he often emphasized in his song lyrics.